Development of an Acid-Base Supplement Book Oriented to Self Regulated Learning (SRL) to Improve Students Metacognitive Skills - Adduriyah Auliya, Safira; Utiya Azizah (International Journal of Educational Research, 2025)
Metacognitive skills in learning are an important indicator that can be measured. Based on the test of metacognitive skills when pre-study obtained the results that the metacognitive skills of learners are still relatively low. One of the learning strategies that can be used to improve the metacognitive skills of learners is a learning strategy oriented self regulated learning (SRL) by utilizing textbooks in the form of supplement books. Therefore, this study aims to describe the feasibility of self-regulated learning (SRL) oriented acid-base material supplement books to improve metacognitive skills of learners. This type of research is Research and Development (R&D) according to the Borg and Gall model. Validity Data obtained through validator assessment using validation questionnaire. Practicality Data obtained through the results of the questionnaire responses of students supported by the results of the observation sheet activities of students. Practicality Data were obtained through pretest and posttest of learners metacognitive skills supported by the results of metacognitive inventory questionnaire. The validation results showed that the content and construct validity criteria were declared valid with a median of 5. Practicality is stated to be practical in terms of the results of the questionnaire responses of students who showed a very strong category with the percentage of content criteria, language, presentation and graphics of 94,25%, 90,67%, 95% and 98,3% respectively with the results of the average percentage of observation sheet activity of students at 96,67%. Effectiveness is stated to be effective in terms of Paired Sample t-test results with sig. values 0.05 and N-gain pretest and posttest scores of metacognitive skills in the high category with the results of the metacognitive inventory questionnaire showed a very strong category with an average percentage of 90,8%. The results showed that the book supplement oriented material acid base self regulated learning (SRL) feasible to use as a solution to improve the metacognitive skills of learners.